Association of Health Service Quality with Patient Satisfaction in Primary Healthcare Center of Gedongtengen Yogyakarta - Yoan Ajeng Mustika; Jacoba Nugrahaningtyas Wahjuning Utami; Sukismanto Sukismanto (JHE: Journal of Health Education, 2019)
Background: Quality of service is an important indicator in measuring patient satisfaction. Based on the results of a preliminary study in 10 patients, in terms of the dimension of reliability quality, 30% said satisfied and 70% less satisfied; in terms of the dimension of empathy quality, 20% said very satisfied and 80% satisfied; in terms of the dimension of assurance, 90% said satisfied and 10% unsatisfied; in terms of the dimension of responsiveness, 10% said very satisfied, 80% satisfied and 10% less satisfied; in terms of the dimension of tangible, 90% said satisfied and 10% less satisfied. the aim of this study is to identify the association between dimension of health service quality and patient satisfaction in Maternal & Child Health and Family Planning Polyclinic at Pimary Healthcare Center (PHC) of Gedongtengen, Yogyakarta.